Avaliação nutricional, genotóxica e atividade antiproliferativa de biomassa microalgal - Barreto, Andressa Ribas (2020)
The increase in the consumption of microalgae as food has led to the need to guarantee nutritious products and free of toxic elements. Thus, this study aims to evaluate the nutritional quality, genotoxicity and antiproliferative activity of the biomass of Spirulina platensis and Euglena sp on the cell cycle of Allium cepa. The proximate composition and the amino acid profile were determined by chemical and chromatographic analysis; the data were analyzed by ANOVA followed by the Tukey test. The genotoxic and anti-proliferative evaluation were performed using the Allium cepa test. Five onion bulbs were used for each control and concentration. From the Spirulina and Euglena biomass, three concentrations 0.15, 0.3, 0.6 g L-1 were prepared with distilled water. The bulbs were rooted in water and subjected to treatments for 24 hours. Subsequently, the roots were collected and fixed in ethanol: acetic acid (3:1) and stored under refrigeration with 70% ethanol until the slides were prepared. The data obtained from the Allium cepa test were analyzed using the Chi-square test. The results show that Spirulina platensis and Euglena sp have an acceptable nutritional quality with high levels of protein and the presence of all essential amino acids. The results of the Allium cepa test showed that Spirulina platensis and Euglena sp have an antiproliferative and non-genotoxic effect in all evaluated concentrations. Both biomasses can be used as food and food supplement for humans and animals. alimento e suplemento alimentício para humanos e animais.